Restoring beauty : the good, the true, and the beautiful in the writings of C.S. Lewis - Markos, Louis (Colorado Springs, CO : Biblica, 2010)
Sections one and two of this book analyze C. S. Lewis's eleven novels, showing how Lewis counters the growing cult of the ugly and helps restore a clearer understanding of the nature of good and evil. Sections three and four turn to Lewis's non-fiction works to assess what advice Lewis can give educators at all levels who would steer their students away from chronological snobbery and values-free education toward a true re-engagement with the past. The book concludes with a commentary on Screwtape's Letters that exposes what Satan's main temptation tactics have been since the 1960s and a bibliographical essay of books by and about Lewis.--From publisher's description.
Part I. Restoring beauty. Fractured fairy tales and the cult of the ugly ; The Space Trilogy I : the beauty of hierarchy ; The Space Trilogy II : the beauty of the normal ; Narnia I : the beauty of complementarity ; Narnia II : the beauty of light and truth ; Till We Have Faces : the beauty of beauty -- Part II. The good guys and the bad guys. The nature of good and evil ; Further up and further down ; Heroes and villains ; Courage along the road ; The heirs of Nietzsche -- Part III. Men without chests. Losing the Tao ; The dangers of a values-free education ; From Tao-less students to Tao-less citizens ; The scientist and the magician ; The chest-less tyrant ; The death of language -- Part IV. Aslan in the academy. Restoring the past ; The renaissance never happened ; Dinosaurs in the classroom ; Genial criticism ; The historical point of view ; The professor as public educator ; Restoring virtue -- Epilogue. Know thy enemy. Screwtape's millennial toast ; Lewis on education and the arts : a bibliographical essay.
Title from PDF title page (viewed on Jan. 3, 2014).
Includes bibliographical references.
Keywords: Lewis, C. S. -- 1898-1963 -- Criticism and interpretation; Aesthetics; LITERARY CRITICISM / European / English, Irish, Scottish, Welsh; Electronic books